Pradofloxacin for Treatment of Bartonella henselae in Experimentally Inoculated Cats - Michael R. Lappin; Ronan Fitzgerald (Pathogens, 2024)
Bartonella henselae is associated with numerous clinical syndromes in people. Cats are the definitive hosts for B. henselae, develop high levels of bacteremia, and are associated with human infections, particularly in the presence of Ctenocephalides felis. Several antibiotic protocols used for the treatment of B. henselae infection in cats have failed to clear bacteremia. The purpose of this study was to assess the safety and efficacy of a high-dose pradofloxacin protocol to eliminate B. henselae bacteremia. Bartonella henselae infection was initiated in 8 cats by intravenous inoculation of infected feline blood and then pradofloxacin was administered at 7.5 mg/kg, PO, twice daily for 28 days, starting 12 weeks after inoculation. Complete blood cell counts were performed prior to pradofloxacin administration and then every 2 weeks for 10 weeks. Bartonella PCR assay was performed prior to pradofloxacin administration and approximately every 2 weeks for 10 weeks and then weekly for 4 weeks. Methylprednisolone acetate (5 mg/kg) was administered by intramuscular injection to all cats on week 10. The cats remained normal and none developed a hematocrit, platelet count, lymphocyte count, or neutrophil count outside of the normal reference ranges. In the one month prior to pradofloxacin administration, all cats were PCR-positive for Bartonella DNA on at least two of four sample dates; after pradofloxacin administration, all cats were negative for B. henselae DNA in blood on all nine sample dates. The protocol appears to be safe and failure to amplify B. henselae DNA from the blood after the administration of pradofloxacin and one dose of methylprednisolone acetate suggests either an antibiotic effect or the organism was cleared spontaneously.